Surgical Management of Dystocia due to Fetal Monster in Dumba Sheep - J Chavda, Karan; M Kapadiya, Falgun; B Solanki, Gajendra; P Patel, Deep; P Patel, Tejas (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Dystocia refers to a difficult birth characterized by prolonged, unassisted labour or a delivery that requires  intervention (Zaborski et al., 2009). In small ruminants,  dystocia occurs less frequently than in large ruminants,  with an incidence of less than 5% (Brounts et al., 2004;  Bhattacharyya et al., 2015). The most common cause of  dystocia in a primiparous ewe carrying a single male lamb  is feto-maternal disproportion (Jackson, 2004). The relative  frequency of the various fetal causes and various types of  malpresentation has also been shown to vary between breeds  (Dwyer and Bunger, 2012). It typically arises when the first or  second stage of parturition is delayed. Most common causes  of dystocia are classified in two categories, viz., maternal  and fetal origin. Fetal dystocia occurs mainly due to faulty  disposition (presentation, position, and posture), congenital  monsters, and foetal pathological condition like ascites and  emphysema. Maternal causes of dystocia mainly include  uterine inertia, weak abdominal straining, incomplete dilation  or constriction of birth canal and inadequate pelvis (David et  al., 2019). Many authors reported that Caesarean section can be  considered an effective way for treatment of dystocia in sheep,  especially when performed early after the onset of the signs of  parturition (Khan et al., 2018; Bruce et al., 2021). The present case  describes the successful surgical management of dystocia due  to foetal monster in a Dumba sheep.
Keywords: Dystocia; prolonged; unassisted; intervention